The Paleogene of East Borneo and its Facies Distribution - Herman Darman (Berita Sedimentologi, 2017)
Paleogene age rocks are exposed over about 40% of Borneo island, mainly in the central or core part. The geologic map shows that more than half of those Paleogene exposures are grouped as a melange unit and the rest are a mix of sediments and meta-sediments. The majority of the melange unit is exposed in Malaysian Sabah and Sarawak. The Paleogene sediments are exposed more in the Indonesian (Kalimantan) side.Within the sedimentary basins around Borneo, the Paleogene interval lies buried deep and is poorly understood. Seismic images covering the Paleogene interval are poor and the number of Paleogene well penetrations is limited. Most well penetrations stopped within the Neogene interval only, where significant hydrocarbon accumulations have been found.Several authors have provided a regional overview of the basins in East Borneo, namely: Barito, Kutei and Tarakan (e.g. Satyana et al., 1999; Darman and Sidi (eds.) 2000 and Netherwood, 2000). Recently the Paleogene in East Kalimantan became a petroleum exploration target (Saller and Vijaya, 2002; Satyana and Biantoro, 1996 and Guritno and Chambers, 1999), unfortunately no significant accumulations have yet been found.This short article summarizes the distribution of Paleogene rocks in the east of Borneo Island based on recent exploration data. A series of proposed paleogeographic maps for the Eocene and Oligocene sections are prepared based on these recent data and understanding. These maps are aimed to facilitate discussions and set up a starting point for further work in the future.